Penilaian Diri Guru terhadap Implementasi Pendekatan Pembelajaran Mendalam dalam Mata Pelajaran Bahasa Indonesia di Sekolah Menengah Pertama di Kota Yogyakarta - Dianastiti, Firstya Evi; Suryaman, Maman; Putri, Titis Kusumaningrum Witdaryadi; Safitri, Ruli Nur (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to determine teachers' self-assessment of the implementation of the deep learning approach in Indonesian language learning. Method in this study using quantitative descriptive research. The teacher assessment scale instrument has been declared valid and reliable. The research subjects were 31 Indonesian language teachers in Yogyakarta City. In the aspect of Learning Partnerships, the largest percentage, namely 51.32% of public respondents stated they were very confident, while in private schools the answer was balanced, 50% stated they were very confident and able to develop elsewhere. The second aspect, in the Learning Environments, the largest percentage in both clusters chose very confident with 51.75% of public respondents and 52.78% of private respondents. Furthermore, in the third aspect of Pedagogical Practices, the largest percentage in both clusters chose very confident with 57.89% of public respondents and 56.94% of private respondents. Then, in the final aspect of Leveraging Digital, the largest percentage in both clusters chose very confident with 57.02% of public respondents and 58.33% of private respondents. Thus, it can be concluded that teacher respondents in both public and private schools in the Yogyakarta City area generally feel very confident in implementing the deep learning approach in the Indonesian language learning process. This study provides empirical evidence that teachers’ high readiness to implement deep learning approaches can enhance meaningful student learning, inform school-level innovation.